The effect of chiral doping in achiral smectic liquid crystals on the de Vries characteristics: smectic layer thickness, electro-optics and birefringence. Issue 4 (16th March 2018) - Swaminathan, V.; Panov, V. P.; Panarin, Yu. P.; Sreenilayam, S. P.; Vij, J. K.; Panov, A.; Rodriguez-Lojo, D.; Stevenson, P. J.; Gorecka, E.
ABSTRACT: An addition of chiral dopant to two achiral smectic liquid crystals from a homologous series, by varying weight percentages with known low values of layer shrinkage, leads to chiral smectic-C* phase with a finite value of the spontaneous polarisation. The electro-optical response arising from changes in the induced apparent tilt angle brought about by a weak electric field in the SmA* phase gives rise to power law dependency on the reduced temperature. The critical exponent γ of the power law depends on the dopant concentration but its value is found to be greater than the typical value of 1.32. This implies that the short-range correlation extends from two dimensions to three dimensions in these materials in the SmA phase. The layer thickness of smectic layers in the guest–host system remains unaltered up to the 15 wt % addition of the chiral dopant to two achiral smectics. The system thus retains the low layer shrinkage of the achiral smectic as evidenced by measurements of the layer thickness from X-ray scattering and thickness measurements from optical interferometry. Results on the optical birefringence and the apparent tilt angle lead us to the conclusion of having successfully obtained chiral smectic materials for devices with de Vries characteristics by chiral doping. GRAPHICAL ABSTRACT: